2020
DOI: 10.1186/s12931-020-01356-6
|View full text |Cite
|
Sign up to set email alerts
|

Different expression levels of interleukin-35 in asthma phenotypes

Abstract: Background: Interleukin (IL)-35 is a newly discovered inhibitory cytokine which is produced by regulatory B and T lymphocytes and belongs to the IL-12 family. It plays a suppressive role in human inflammatory diseases; however, its role in asthma phenotypes is unclear. Our study focuses on the sputum IL-35 level in patients and investigates different airway inflammation capacities of sputum IL-35 in patients with different asthma phenotypes. Objective: We aimed to determine the sputum IL-35 levels in asthmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Prior studies have explored the interactions between IL-35 and other intratumoral immune cell populations not discussed above, such as neutrophils, MDSCs, and NK cells (88)(89)(90), although more research on these interactions is warranted. Antitumorigenic N1 neutrophils and pro-tumorigenic N2 neutrophils are two different subsets of neutrophils identified in previous studies (91).…”
Section: Interactions Between Il-35 and Other Immune Cells In The Tmementioning
confidence: 99%
“…Prior studies have explored the interactions between IL-35 and other intratumoral immune cell populations not discussed above, such as neutrophils, MDSCs, and NK cells (88)(89)(90), although more research on these interactions is warranted. Antitumorigenic N1 neutrophils and pro-tumorigenic N2 neutrophils are two different subsets of neutrophils identified in previous studies (91).…”
Section: Interactions Between Il-35 and Other Immune Cells In The Tmementioning
confidence: 99%
“…Generally, hepatitis B virus (HBV) and hepatitis C virus (HCV) were common in liver injury, both of which were non-cytopathic virus ( Gonzalez and Gordon, 2020 ; Spyrou et al, 2020 ). It has been reported that IL-35 was associated with significant inflammation inhibition, which can inhibit the proliferation of T cell and the function f its effector ( Li et al, 2020a ). This compelling function pushed us to figure out the theoretical basis and other beneficial effects of IL-35 in the immune-pathogenesis of HBV, HCV hepatitis, and autoimmune hepatitis (AIH).…”
Section: The Roles Of Interleukin-35 In Liver Diseasesmentioning
confidence: 99%
“…Notably, due to an increase of TNF-α mRNA and protein expression in the airways of asthmatic patients, it was raised the possibility of TNF-α participating in the dysregulation of the inflammatory response in the asthmatic airways [ 11 ]. Meanwhile, the study found that IL-35 participated in the pathogenesis of asthma some inflammatory and autoimmune diseases, including asthma, by brokering the inhibition of effector T cells [ 6 , 12 ]. However, studies regarding the role of IL-35 on cell pyroptosis and often occurring in inflammatory diseases are not yet clarified.…”
Section: Introductionmentioning
confidence: 99%